Rainwater use in low income housing - Barreto, D. (2010)
ABSTRACT: This paper presents the results of a study conducted in low income housing (Social Housing Buildings) in order to identify the potential use of rainwater, considering the two types of houses built up by a state company that provides large scale low income housing in the state of Sao Paulo, Brazil. It was studied the water consumption of sanitary appliances and was identified which appliances could be supplied by rain water. Following, were selected two main types of houses among all housing built: one level storey houses and multi-storey buildings (apartments). These types of houses are located in different cities in Sao Paulo state. Next step was a weather study about two cities in order to find out the rain periods quantities and frequency. Based on a methodology cited by Brazilian standard, but very similar to European practice for designing volumes of rainwater capture, it was done a balance of water needed to supply the sanitary appliances for each house type. A series of calculations were performed and it was found the water volumes needed to supply the houses related to percentage water economy and its contribution along drought season. In terms of potential water volume saved was found that rainwater can be used in one storey house for WC cistern flush and clothes wash machine remaining 1,92 m3/month and reaching an economy of 1.063,8 m3/year, for 45 units studied and a saving of 5.977 US$ per year. For apartment buildings there were two findings: one with rainwater reservoirs at ground level and the rain water pumped up to be used for WC cistern and clothes wash machine yielding a year economy of 5.068,8 m3. Another finding was that the rainwater is reserved in the roof level, feeding only WC cistern. This alternative comes up a year economy of 4.630,08 m3. In monetary terms it represents savings respectively of 15.933 US$ and 14.500 US$ per year. The results pointed out the feasibility in terms of rainwater volumes to be used and identified the relationships between volumes of necessary rainwater and complementary potable water in percentage terms, so resulted in compatible reservoir sizes for use without affecting the building structures or costs. Also, some design options for rainwater systems for each kind of type buildings were developed.